An Analysis of American Dream in Chang-Rae Lee’s Dystopian Novel on Such A Full Sea - Gitami Ayuningdiah (Universitas Pendidikan Indonesia (UPI), 2016)
This study explores the idea of American Dream in Chang-Rae Lee’s dystopian novel entitled On Such A Full Sea. It examines how American Dream manifests in the text. To meet the purpose, Cullen’s (2009) theory and indicators of American Dream are used for this research. This research uses qualitative approach in form of textual analysis. The findings reveal that American Dream is not static, as it is always changing. American Dream in the text manifests through the formations of negotiations. These negotiations are in forms of alternatives for their American Dream that appears through the characters’ process of self-learning as they go through their life journey. It is found that there are three out of four indicators of American Dream that appear in the text: freedom, equality, and upward mobility. This study also finds that according to the text, happiness can be attained, even though the American Dreams mentioned are not achieved. Through the characters’ process of self-learning, it is found that being useful for people around, being thankful for what is already owned, and being with loved ones in tough times can result in happiness.Keywords: American Dream, freedom, equality, happiness, upward mobility, dystopian literature